Diseño de bisutería a partir de residuos de cuero del sector del calzado en la provincia de Tungurahua - Chicaiza Mangui, Ligia Esthela (2025)
Footwear companies in the city of Ambato generate different types of waste, with leather being the main waste with a high percentage. This waste is commonly disposed of in landfills, which generates environmental contamination; therefore, it is essential to consider these materials in the use or manufacture of new products that contribute to waste minimization. Therefore, this research work aims to analyze and reuse this material in the development of costume jewelry pieces, in order to reincorporate this material to sustainable production processes and where these wastes are used, in addition to minimizing the waste generated. The data obtained from the research applied to the footwear companies show that it is important to take into account several characteristics that allow selecting the appropriate leather waste for the development of new products, because there are different ways of classification and storage that depend on each company, in addition to the information collected by the jewelry designers, where it is observed that there are different tools and techniques for the production of the same. Therefore, through the data obtained from both footwear companies and costume jewelry designers, the development of costume jewelry pieces using leather waste as raw material was proposed, allowing the material to be reincorporated into new products and generating functional, aesthetic and sustainable pieces, allowing users to become involved in the process of customizing pieces, as well as understanding the importance of reusing alternative materials to develop new products.